Strategi Aktor Politik Baru dalam Pembanguanan Infrastruktur di Kecamatan Nusa Penida Kabupaten Klungkung 2016 - Puspawati, Ni Wayan; Erawan, I Ketut Putra; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2018)
ABSTRACT The struggle of political actors has been viewed by various parties in fighting for the people of Klungkung Regency, especially the District of Nusa Penida. What is the strategy of new political actors in the development of infrastructure district Nusa Penida Klungkung district 2016. The theory used in the research is the theory of political elite, and Rational Choice where the method used is qualitative in obtaining interviews with sources. The results in the study there is a politics of repayment to klungkung mainland that only needs to be maintained Meanwhile, in Nusa Penida needs to be built because there is no decent development for the local community. Support from the central figure in Nusa Penida work together in developing development so that the positive impact where both parties mutually benefited in infrastructure development. Keywords: Political actors, Regional Elites, Infrastructure development